The Role of Inclusive Education Curriculum Management in Realizing the Quality of Education - Pratama, Awal; Febrianti, Ina; Alinur, Armayanti; Syahril, Syahril (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2023)
This study aims to describe the relationship between curriculum management and the quality of inclusive education at SMP Negeri 8 Watampone. Using a qualitative descriptive method with a field research approach, data were collected through observation, interviews, and documentation. The results show that inclusive curriculum management involves structured planning, implementation, and evaluation, tailored to meet the needs of students with special needs. Planning includes lesson plans, individualized education programs (IEPs), and class administration. Implementation highlights the importance of communication, learning modification, and teacher adaptation to diverse student needs. Evaluation is conducted both formally and informally to monitor student progress. Furthermore, input, process, and output indicators reflect the school’s efforts in recruiting, supporting, and evaluating inclusive education. The study concludes that effective curriculum management significantly contributes to improving the quality of inclusive education through well-coordinated resources, competent teachers, and responsive learning environments.